Adaptive responses of Jerusalem artichoke to mid-season drought: effects on phenolic compounds and p-coumaric acid content - Ruttanachira Ruttanaprasert; S. Jogloy; Anon Janket; Patthraporn Siripipatthana; Thanaset Senawong; Chorkaew Aninbon (BMC Plant Biology, 2025)
BACKGROUND: Drought stress can influence the accumulation of phenolic compounds in plants. This study investigated the adaptive response of Jerusalem artichoke to mid-season drought stress, focusing on changes in total phenolic content and p-coumaric acid contents. METHODS: A pot experiment was conducted using a 2 × 5 factorial arrangement in a randomized complete block design with three replications. Factor A comprised two irrigation treatments: field capacity (FC) and mid-season drought stress (maintaining 50% available soil water [50% AW] from 31 to 60 days after transplanting). Factor B included five Jerusalem artichoke genotypes with varying levels of drought resistance: JA 3, JA 125, JA 15, JA 89, and CN52867. RESULTS: Mid-season drought significantly decreased leaf relative water content at 60 days after transplanting of Jerusalem artichoke in both years (73.2% in year 1 and 74.2% in year 2). Drought significantly affects total phenolic content in leaf and stem at 90 DAT but does not affect TPC in tuber. Genotype JA 125 showed high total phenolic content under drought conditions in leaf (38.3 mg GAE/g dry weight), stem (24.3 mg GAE/g dry weight) and tuber (9.0 mg GAE/g dry weight), especially in the second year. The JA3 genotype showed stability for increased accumulation of total phenolic contents under drought stress and this genotype also accumulated the highest p-coumaric acid (15.4 mg GAE/g dry weight) under drought stress. These findings highlight the potential of Jerusalem artichoke as a source of bioactive compounds and these genotypes can serve as breeding sources to enhance the drought resistance and high phenolic content of Jerusalem artichoke.
Keywords: Microbial Metabolites in Food Biotechnology; Cynara cardunculus studies; Plant Growth Enhancement Techniques